Cadmiumtoxicity in plants - Vieira, Licielo Romero; Corrêa, Emerson Silveira; Moraes, Beatriz Stoll; Rossato, Marivane Vestena; Vestena, Silvane (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Phytoremediation is a technique that uses plants for decontaminating polluted areas, as soil and water, especially from heavy metals and organic contaminants, reducing their concentration to safe levels. In addition, it contributes to improve physical, chemical and biological characteristics of these areas. Among the several forms of environmental contamination resulted from industrial and agricultural activities, water contamination with heavy metals has been the one causing more concern to researchers and government institutions involved to pollution control. Cadmium (Cd) is one of the heavy metals more studied due to its high toxicity to plants and animals. In response to the stress caused by Cd, plants can develop many tolerance mechanisms which can operate sometimes as additional mechanisms. Two possible mechanisms can be the activation of the antioxidant system and/or changes in sulfur metabolism, specially glutathione, an essential substrate to phytochelatins (PC) biosynthesis. Rivers and dams have been being contaminated with heavy metals and other contamination forms due to urban and industrial discharges. Part of heavy metal elimination and/or contamination detection can be done using aquatic plants as Eichhornia crassipes (Mart.) Solms and Salvinia auriculata (Aubl.).